Volatility links between US industries - Ben Sita, Bernard (2013)
This article investigates volatility linkages across 30 US industries in terms of volatility leadership impact and interdependence dynamics. The volatility spillover index of Diebold and Yilmaz (2009 Diebold, F. X. and Yilmaz, K. 2009. Measuring financial asset return and volatility spillovers, with application to global equity markets. Economic Journal, 119: 158–71. [CrossRef], [Web of Science ®] ) is used to uncover industries that show leadership in volatility and to measure the impacts of leading industries on lagging industries. I find that a leader is also a follower, which results into a web of complex relationships in volatility spillovers. Nevertheless, I identify the business equipment, the manufacturing and the financial intermediation industry as the main leading industries through which the entire economic system can be either stimulated when the economy is contracting or cooled when the economy is expanding.